Foundations of perturbative QCD - Collins, John Clements (Cambridge : Cambridge University Press, 2011)
Kazalo.
Bibliografija: str. 603-616. -
Keywords: quantum chromodynamics -- nuclear physics -- quantization -- renormalization -- Libby-Sterman analysis -- parton theory -- hadron-hadron collisions